The Legality of the Prostitution Place Behind the Nightlife - Andi Hidayat Anugrah Ilahi; Titien Pratiwi Adnas (Faculty of Law, Universitas Muslim Indonesia, Indonesia, 2021)
The rampant localization of prostitution that moves implicitly on the Nusantara Street of Makassar causes a long-standing problem that is neglected in terms of legislation, sexually transmitted diseases, and human trafficking. This study aims to provide information about raising social reality through case studies of the relationship between commercial sex workers and nightclubs (THM) on Nusantara street, as well as an observation of the phenomenon of pimps, customers, and commercial sex workers in the Indonesian legal system, and comparison on the perspectives of the government and local regulations in the City of Makassar. The method used in this research is depth interview, observation, and literature review. The findings indicate that there is a mutual relationship between nightclubs (THM) and prostitution activities and that they even benefit each other. In addition, the existence of Regional Law Number 4 of 2014 On the Supervision and Control of the Procurement, Distribution, and Sale of Alcoholic Beverages shows that there is no firm step taken by the local authorities to minimize the activities of nightlife entertainment and hidden prostitution.